Chronic carotid glomitis and the glomus pulmonale. Issue 1 (January 1990) - Khan, Q; Heath, D
Abstract : A histological study was made of the carotid bodies and glomus pulmonale in 50 consecutive subjects over the age of 50 years who came to necropsy to determine if chronic glomitis is confined to the carotid bodies or whether it also occurs in other glomera. Lymphoid aggregates and plasma cell activity were found in the glomus pulmonale just as they were in the carotid bodies. Chronic pulmonary glomitis sometimes occurred in association with chronic carotid glomitis and sometimes independently of this. The mean age of the affected subjects was 76 years in isolated pulmonary glomitis and 79 years in chronic carotid glomitis. Chronic carotid glomitis affected seven (14%) subjects and predominated in women (six to one). In the seven cases of isolated pulmonary glomitis women predominated five to two. Chronic glomitis seems to be a disease process which may affect at least two members of the non-chromaffin paraganglionic system, but it is not clear why focal chronic inflammation affects the glomus pulmonale of one person but not of another.